Cytopathological examination of the cerever in pregnant women: An integrative review (Research, Society and Development, 2020)
The objective was to analyse in scientific evidence the factors that contribute to pregnant women who do not adhere to the cervical cytopathological examination during pregnancy. An integrative literature review study was carried out by searching the VHL, SciELO, Pubmed and Google academic databases in the period from 2015 to 2019. The keywords “Papanicolau”, “Uterine Cancer” and “Pregnant women” were used. A total of 6.973 articles were selected, soon after the inclusion criteria were applied and 1.739 were selected for reading titles and abstracts. After this reading, 10 articles were selected that met the research objective to compose the work. The results of the study showed that socioeconomic factors, fear, insecurity, lack of information on the exam and its importance in the gestational period for the prevention of uterine neoplasms by the nurse professional, contribute to a low demand and adherence to the exam. It is concluded that pregnant women need to know the cervical cytopathological exam and its importance during pregnancy, in order to be able to adhere to the exam practice. Thus, it is necessary to train professional nurses in addition to implementing strategies to positively change this scenario.